Fossil-bearing Citalang Formation, Sumedang-Majalengka, West Java - Rizal, Yan (Berita Sedimentologi, 2021)
The Citalang Formation in Sumedang-Majalengka area comprises of various lithological units, including coarse-grained sandstones to conglomerates, greenish grey to dark grey claystone with sandstone and tuff interbeds, and pumice-bearing tuffaceous sandstones and tuff. All these units occur in the lower part of the formation and the contacts with older, underlying rock units are unconformable in several places.Vertebrate fossil fragments are frequently found in the lowermost part of the formation, especially within the coarse-grained sandstones to conglomerates unit. This unit also holds stone tools artefacts, which were made from different kind of stones and show quite simple or primitive shape. The age of Citalang Formation is not yet resolved and still needs to be researched. Some published literatures suggest Pleistocene while there are others that suggest Pliocene.